Development of the internal public. A proposed methodology for an educational program aimed at museum employees (2013) (Cadernos de Sociomuseologia, 2014)
This study addresses issues of importance and relevance to the topic of the thesis - development of methodology for an educational program aimed at the internal audience of the museum - and reinforce the understanding that the educational character of the museum should be practiced at different levels of the institution. The reflections proposed are based mainly on the ideas of Paulo Freire Reglus Neves (1988), the museologist Waldisa Russio Camargo Guarnieri (1984), the museologist and educator Maria Célia Teixeira Santos Moura (2008). We propose the creation of a methodology for an educational program aimed at the museum’s workers with emphasis on the professional and personal development through educational activities designed together from a diagnosis, common goals and assessment practices. Intended to develop a methodology that serves as an experimented script in order to facilitate action, minimize errors, aid the communication and understanding about the actions; composed of references, procedures and steps that facilitate planning, development and evaluation, and contribute to the construction of a dialogue between employees. The methodology was applied in the National Museum of Natural History and Science, at the city of Lisbon.Keywords: Museology and Education, Education in Museums, Educational Action in Museums, Educational Action for Staff of Museums; Internal Audience of Museum.